1992
DOI: 10.3171/jns.1992.77.1.0015
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and intracranial pressure-volume dynamics in severe head injury: relationship with cerebral blood flow

Abstract: Increased brain tissue stiffness following severe traumatic brain injury is an important factor in the development of raised intracranial pressure (ICP). However, the mechanisms involved in brain tissue stiffness are not well understood, particularly the effect of changes in systemic blood pressure. Thus, controversy exists as to the optimum management of blood pressure in severe head injury, and diverging treatment strategies have been proposed. In the present study, the effect of induced alterations in blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
1
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(113 citation statements)
references
References 27 publications
(5 reference statements)
3
105
1
4
Order By: Relevance
“…The HR may increase first, inducing a short increase of CBF (17), and in turn the increased CBF will bring more oxygenated hemoglobin, reduce the concentration of deoxyhemoglobin, and generate a positive BOLD signal. However, such a transient change in cerebral perfusion pressure or arterial blood pressure is autoregulated by either vasoconstriction or vasodilatation, resulting in altered vascular resistance so that CBF remains more or less constant (18). The weak, scattered, and transient BOLD signal changes may reflect such an autoregulation process.…”
Section: Discussionmentioning
confidence: 99%
“…The HR may increase first, inducing a short increase of CBF (17), and in turn the increased CBF will bring more oxygenated hemoglobin, reduce the concentration of deoxyhemoglobin, and generate a positive BOLD signal. However, such a transient change in cerebral perfusion pressure or arterial blood pressure is autoregulated by either vasoconstriction or vasodilatation, resulting in altered vascular resistance so that CBF remains more or less constant (18). The weak, scattered, and transient BOLD signal changes may reflect such an autoregulation process.…”
Section: Discussionmentioning
confidence: 99%
“…4,21 Disturbed cerebral autoregulation has been shown to occur in patients after head injury, and in experimental models it has been observed even when the values of CPP and CBF are normal.…”
Section: Pathophysiology Of Cerebral Autoregulation In Tbimentioning
confidence: 99%
“…Autoregulatory vasoconstriction predominantly takes place in the largest arterioles (> 200 µm in diameter), although the bulk of the CBV is probably contained in smaller vessels, because they are so much more numerous, and in the venous system. 4 Additionally, endothelium-related factors have been suggested to contribute to autoregulatory responses, and some studies have indicated a possible role for NO as a vasodilator during reduced CPP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, quantification of CBF alone cannot define the relationship between oxygen supply and consumption because the adequacy of oxygenation is also determined by variables such as autoregulation, CO 2 reactivity, and coupling of CBF and cerebral metabolism that are disturbed in a significant number of head-injured patients. [2,3,9,14,26,34,36] Furthermore, confounding variables such as vasospasm, anemia, hypoxia, and seizures may reduce the oxygen carrying capacity. A measure of the balance between cerebral oxygen delivery and consumption, such as AVDO 2 , may therefore be useful and, when combined with multimodality monitoring, may provide a reasonable means to identify patients in which secondary ischemic damage can be ameliorated by therapeutic intervention directed at its pathophysiological mechanism.…”
Section: Applications For Jugular Oxygen Monitoringmentioning
confidence: 99%